EFEKTIVITAS PEMANFAATAN LIMBAH PRAKTEK LABORATORIUM PENDIDIKAN TATA BOGA JURUSAN PENDIDIKAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI SEMARANG - Astuti, Romiyatun Mijiling; Lestari, Noer Hayati (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2017)
Activity on campus especially dilaboratorium practice activity produce enough garbage anddiverse. Catering laboratory practice activities produce lots of wet garbage or green garbage that contains a lot of nitrogen, while garbage yard including dry waste / brown which contains carbon. During this waste is thrown away just to the trash. Penaliti wants to use this waste to be a more useful item of compost. The purpose of this research is to know: compost quality; how long the composting process; how much nitrogen content and carbon from compost result of waste of practice and garbage yard.This research includes laboratory experimental research, located in the laboratory of Culinary Engineering Department of PKK, Faculty of Engineering UNNES, with practical research materials and page E7. The research procedure is X1 of brown and green mixed waste material with 3: 1 ratio, X2 brown waste material, and X3 green waste material. Observed changes are; temperature, composting time, color, odor, N content and grade C. Data collection technique using observation of change during composting process and chemical test of C content with AOAC test method 967.05.2000 and N content with Kjeldahl test method.The results showed that the composting temperature ranged between 28oC- 40oC. The time spent on composting brown waste is longer than green and mixed waste. The smell of green garbage stinks / ammonia, mixed garbage and brown rubbish does not cause bad smell. Nitrogen content of 0.14% mixed waste compost, 0.23% cocoa waste compost and 0.27% green garbage compost. Carbon compost content of mixed waste 1.43%, compost 8.72% chocolate waste, and compost 7.72% green garbage.